Predictive Performance of the Braden Scale and Additional Clinical Risk Factors for Pressure Ulcer Development in Intensive Care Patients: An Observational Study - Dr Ezhilbharathi; Dr. Sasikumar; Dr. Karthikeyan; Dr. Kambala prasanna kumar (The Bioscan, 2026)
Background: Pressure ulcers remain an important concern among critically ill patients. The Braden Scale is widely used for risk assessment; however, its predictive performance may vary across clinical settings. This study evaluated the performance of the Braden Scale and explored additional factors associated with pressure ulcer development among ICU patients. Methods: This hospital-based observational study included 50 critically ill patients recruited consecutively. Braden Scale assessments were performed within 24 hours of ICU admission, and patients were monitored for pressure ulcer development. Clinical, ICU-related, and preventive care factors were assessed. ROC analysis evaluated discriminative performance, while univariable Firth penalised logistic regression identified factors associated with pressure ulcer development. Results: Ten patients (20%) developed pressure ulcers. Their median Braden score was significantly lower than that of patients without pressure ulcers (10 vs. 17; p<0.001). All pressure ulcer cases occurred among patients classified as high or very high risk. The Braden Scale demonstrated an AUC of 1.000, with an optimal cut-off of 12.5 and apparent sensitivity and specificity of 100%. Each one-point increase in Braden score was associated with 74% lower odds of pressure ulcer development (OR=0.26; 95% CI: 0.06–0.49; p<0.001). Conclusion: The Braden Scale demonstrated strong apparent predictive performance among ICU patients. Larger multicentre studies are required to validate these findings.